МЕТОДОЛОГІЧНІ ОСНОВИ ДЕРЖАВНОЇ ІНФОРМАЦІЙНОЇ ПОЛІТИКИ УКРАЇНИ - Butyrsky, Oleksandr (Zhytomyr Ivan Franko State University, 2024)
The article provides a comprehensive analysis of the state information policy’s methodological foundations of in Ukraine. It also analyzes current scientific probles. It consists in the state policy’s scientific substantiation of the methodological foundations in the sphere of mass communication in the conditions of social changes in Ukraine. It is substantiated that the improvement of the state information policy in the process of its development and implementation requires taking into account the national cultural identity of the national information space. Without preserving national cultural identity, the integrity and independence of the nation-state become problematic. It was clearly confirmed by the events in Crimea and eastern Ukraine, which escalated into a full-scale Russian-Ukrainian war. It becomes obvious, that without taking into account the cosmopolitan trends of the information society and global culture, there is a threat of the national information space isolation. All of these can cause the displacement to the periphery of the socio-political and economic life of the modern world. At the stage of information warfare the most important task is to use the capabilities of the mass media to mislead a potential enemy, discredit its military-political leadership and leaders, and limit the enemy apos. The same must be done with information and propaganda activities, up to and including organizing an information blockade. A comprehensive analysis of the mass media activities during election campaigns in Ukraine has demonstrated the need for the legislator to define clearly the requirements for the general principles of information support for the electoral process. Without clear criteria for "impartiality", "balance", "completeness" and other concepts, the assessment of election coverage turns into an assessment of the methods used to measure the information activities of the mass media during elections in Ukraine. It has been established that ensuring the right to receive public information from state authorities and other managers of public information is a key principle of state policy. This policy is aimed at increasing the level of transparency and openness of the state activities and local self-government. It also prevents corruption, public participation in state administration and decision-making. These measures require a comprehensive analysis of the latest vectors of the state's information policy implementation, the principles and instruments of ensuring the right of access to public information, (defined by the Law of Ukraine "On Access to Public Information"), and the search for effective mechanisms for its practical implementation.